Optimum bolus wizard settings in insulin pumps in children with Type 1 diabetes. Issue 10 (5th February 2016) - Andersen, A. J. B.; Ostenfeld, A.; Pipper, C. B.; Olsen, B. S.; Hertz, A. M.; Jørgensen, L. K.; Høgsmose, J.; Svensson, J.
Abstract: Aim: To evaluate current insulin pump settings in an optimally regulated paediatric population using bolus wizard. Methods: We used a retrospective study design to analyse data from 124 children on insulin pump therapy who had optimum HbA1c levels [< 59 mmol/mol (< 7.5%)] and no history of severe hypoglycaemic events. Bolus wizard settings were used to calculate the insulin to carbohydrate factors and insulin sensitivity factors. Multiple regression analysis was used to analyse the variables associated with the calculation factors. Results: Insulin to carbohydrate factor varied from 276 in the youngest group to 424 in the oldest group, and increased according to age. Insulin sensitivity factor was highest in the group aged 6 to < 12 years, with a value of 125. Age, amount of carbohydrates, number of boluses per day and insulin per kg were all significantly associated with both calculation factors. Furthermore, duration of insulin pump treatment was significantly associated with insulin sensitivity factor and percentage bolus/basal was significantly associated with insulin to carbohydrate factor. Gender, diabetes duration and BMI were not associated with any of the calculation factors. Conclusion: Optimum insulin pump settings at pump initiation depend on both insulin requirements and use of the pump. Settings need to be individualized because the standardized calculation factors are not constant for children. There is a need to develop specific age‐ and insulin dose‐dependent calculation factors. What's new?: We found age‐related and insulin dose‐dependent differences in optimum insulin pump settings. Bolus wizard settings need to be individualized because standardized calculation factors are not constant for children. The insulin to carbohydrate factor corresponding to the '500 rule' and the insulin sensitivity factor corresponding to the '100 rule' is not applicable in children. Optimum pump settings at initiation of pump treatment and adjustment to these settings as children grow may increase treatment adherence. Further prospective studies on calculation factors and metabolic control are needed.